A Comparison of the Effectiveness of Four Exercise Machines in the Development of Health Related Fitness among Women in Universiti Putra Malaysia - Kok, Lian Yee (1998)
In order to compare four modes of exercise in improving health-related fitness, 119 women from Universiti Putra Malaysia (mean age = 28.77 years) were randomly assigned to control or four experimental groups. The experimental groups completed ten weeks of training frequency set at three days per week, with one group being the control, and one group each training on one type of exercise machine. The exercise machines used were the Treadmill, the Body Tone II, the Gravity Walker and the OrbiTrek. Pretest and posttest were performed on ten measures representing the five healthrelated fitness components. Measures were taken on estimated V02 max, l-RM bench press, l-RM leg press, back strength, bench press repetition, leg press repetition, standing trunk flexion, trunk and neck extension, hip flexion, and percent body-fat. Analysis of variance (ANOVA) was performed on the difference between pretest and post test scores. This was followed by Tukey's post hoc test. F tests indicated that all four exercise machines elicited significantly higher scores than the control on all measures (F4,1l4 =2.45, P <.05) except for l-RM leg press, leg press endurance and percent body-fat. No significant changes were observed for percent body-fat among all groups. For the l-RM leg press and leg press endurance, the Treadmill group did not show significant improvements when compared to the control or the other experimental groups. However significant differences were not observed among the experimental groups. These results suggest that training on the four exercise machines was associated with significant improvement in all of the health-related fitness components with the exception of body composition. However, there appears to be no advantage of using any one of the machines over the others to improve physical fitness of previously sedentary women.